Comparative Analysis of Traditional and Modern Make Up Artists (MUAs) Integrated with Wedding Organizers in Jember Regency - Indah Cindiyana; Roro Aditya Novi Wardhani; Harmawan Teguh Saputra (University of Muhammadiyah Malang, 2026)
This study examines the competitiveness of traditional and modern Make Up Artists (MUAs) integrated with Wedding Organizer (WO) services in Jember Regency. The research focuses on pricing, business location, digital marketing strategies, and socio-cultural dynamics influencing market competition. A qualitative descriptive method was applied using SWOT analysis. Data were collected through interviews, observation, and documentation involving traditional MUAs (Nadine Salon) and modern MUAs (Sriwijaya Salon). The results show that traditional MUAs possess strong cultural capital in the form of inherited skills, local trust, and cultural authenticity, supported by affordable pricing but limited digital adaptation. In contrast, modern MUAs demonstrate higher competitiveness through integrated services, digital marketing utilization, and alignment with contemporary consumer preferences, although they face high operational costs and intense digital competition. Sociologically, these differences reflect shifts in consumer behavior, generational preferences, and the growing influence of digital platforms in shaping service selection. The study concludes that sustainable competitiveness requires a balance between technological adaptation and socio-cultural sensitivity. Traditional MUAs need selective digital integration without losing cultural identity, while modern MUAs should strengthen personalized and culturally responsive services. The findings provide practical insights for SMEs and policymakers in supporting a competitive and culturally inclusive beauty service industry.